A-120 Comparison of Baseline and Post-Concussion ImPACT Performance in Spanish-English Bilingual and English Monolingual Athletes. (30th August 2021) - Rogers, Erick; Kuwabara, Hana; Goodwin, Grace; Moore, Sara; Hopkins, Nia; Goto, Amber; Maietta, Julia; Ross, Staci; Kinsora, Thomas; Allen, Daniel
Abstract: Objective: Research comparing English and Spanish administrations of Immediate Post-Concussion Assessment and Cognitive Testing (ImPACT) have consistently found differences in performance on various cognitive composites. Few studies have examined the effect of bilingualism on baseline and post-concussion assessments. This study examined whether monolingual English-speakers (MO) and bilingual Spanish/English speakers (BI) differed in cognitive performance at baseline (BL) and post-concussion (PC). Methods: Participants were selected from a larger database of high school athletes administered ImPACT in English at BL and PC. Participants included 86 BI athletes (Mage = 14.53; 65.10% male) and 86 MO athletes matched on age, gender, sport type, and probable concussion as defined by number of PC follow-up assessments (PCF; 0 vs. ≥1). To examine group differences and changes over time in cognitive composites, a general linear modeling approach was used with language and PCF as between-subjects factors and time as a within-subjects factor. Results: There was a significant Language x Time x PCF interaction for Visual Memory (VM), Visual Motor Speed (VMS), and Reaction Time (RT). On VM and RT, MO with multiple PCF performed the worst at PC, while MO with 0 PCF performed the best at PC. On VMS, BI with 0 PCF performed the worst at BL. Conclusion: Visual memory and reaction time were less affected in bilingual compared to monolingual athletes with probable concussion. However, at baseline, bilingual athletes had slower visual motor speed compared to monolingual athletes. Future research should focus on how bilingualism may serve as both a protective and risk factor for cognitive functioning after probable concussion.